Development of Scalable Elastic Gelatin Hydrogel Films Crosslinked with Waterborne Polyurethane for Enhanced Mechanical Properties and Strain Recovery - Soon Mo Choi; Eun Joo Shin; Sun Mi Zo; Madhusudana Rao Kummara; Chul Min Kim; Anuj Kumar; Han Jo Bae; Ankur Sood; Sung Soo Han (Gels)
Exploiting novel crosslinking chemistry, this study pioneers the use of waterborne polyurethane (WPU) to chemically crosslink porcine-derived gelatin, producing enhanced gelatin hydrogel films through a solvent-casting method. Our innovative approach harnesses the reactive isocyanate groups of WPU, coupling them effectively with gelatin’s hydroxyl and primary amino groups to form robust urea and urethane linkages within the hydrogel matrix. This method not only preserves the intrinsic elasticity of polyurethane but also significantly augments the films’ tensile strength and strain. Comprehensive characterizations of these hydrogel films and pre-formed hydrogel reaction mixtures were conducted using viscosity measurements, Fourier Transform Infrared Spectroscopy (FTIR), Thermogravimetric Analysis (TGA), and the universal testing machine (UTM) for tensile-recovery assessments, alongside evaluations of their biocompatibility. The results demonstrated a reduction in pore size with an increase in WPU concentration from 2 to 6% in the developed hydrogels with a decrease in the equilibrium swelling ratio from 15% to 9%, respectively. Further, hydrogels with 6% WPU exhibited the highest tensile stress in both a dry and wet state. The gelatin hydrogel formed with 6% WPU blend also demonstrated the growth and proliferation of CCD-986K (fibroblast) and CCD-1102 (keratinocyte) cells for up to 5 days of co-culturing. The results indicate a notable enhancement in the mechanical properties and biocompatibility of gelatin hydrogels upon the introduction of WPU, positioning these films as superior candidates for biomedical applications such as tissue engineering and wound dressing.